The Influence of the Problem-Based Learning Model on Metacognitive Knowledge and Science Learning Outcomes - Gamar B. N. Shamdas; Abd. Hakim Laenggeng; Abdul Ashari; Rizka Fardha (Jurnal Penelitian Pendidikan IPA, 2024)
Metacognitive knowledge refers to what is known about memory function and the strengths and weaknesses of one's own cognition. This research aims to describe the influence of the problem-based learning model on the metacognitive knowledge and learning outcomes of class IX junior high school students. The research was carried out on Class IX students of Palu City Middle School, the entire population of Class IX consisted of three classes with a total of 45 students. Two classes were used as samples determined based on purposive sampling. Metacognitive knowledge data was obtained through questionnaires and learning outcome data through essay and multiple choice tests. Data analysis used an independent t-test with the help of SPPS version 25.0. The results showed that metacognitive knowledge with conventional learning was significantly lower than the PBL class with a gain of t(25) = 9.289, p < 0.000 and learning outcomes in the conventional class were significantly lower than the PBL class with a gain of t(25) = 4.520, p < 0.000. The conclusion of this research is that there is an influence of the problem-based learning model on the metacognitive knowledge and learning outcomes of class IX SMP students